Ethics in Research - Gregory, Ian; Andrews, Richard (London Continuum, 2005)
This book encourages reflection upon the inescapable ethical dimensions of the conduct of research. Gregory explores how ethical concerns inform not only the conduct of research but how they enter into the very decision to engage in a piece of research, the interpretation of data and what is done with research findings. Issues arising from the reflections of the text will be brought to bear upon the character of the researcher, the place (if any) of codes in practice for researchers and whether if in deference to ethical considerations there are limitations upon what can be countenanced in the name of research
Keywords: Ethics -- Research Methodology